Repairing the loss of the past: the use of written, oral and physical evidence in the Ecclesiastical History of Orderic Vitalis (c.1113−42). - Rozier, Charles C. (Historical Research, 2019)
This article examines attitudes to sources in the Ecclesiastical History of Orderic Vitalis (c.1113−42). It is argued that as an experienced student of writing history, Orderic had learned to privilege written accounts over oral sources when dealing with the distant past. It is demonstrated that when a shortage of written accounts forced him to draw on longstanding oral traditions for events up to 500 years before his own time, Orderic introduced these accounts with discomfort, and sought to evaluate what he had heard with analogous written sources and physical (archaeological) remains. Orderic's discourses on the nature, use and limitations of his sources are used to build a picture of how much Orderic felt it was possible to know about the past, how he attempted to reconcile the gaps in what could be known and, ultimately, how he imagined his role as historian.